Liquid crystal formation in mixtures of metal alkanoates: gadolinium-containing binary systems - Zavora, L.N.; Panikarskaya, V.D.; Kasian, N.A.; Bedrik, A.I.; Shershukov, V.M.; Lisetski, L.N.; Mirnaya, T.A. (Functional Materials, 2007)
Mesophase formation is reported in ionic liquied crystal mixtures of lead decanoate with gadolinium alkanoates. The negative effect of Gd salts on mesophase thermal stability increased in the order stearate < undecanoate < 2-ethylhexanoate, with gadolinium-containing mesophase persisting on introduction of the non-mesogenic Gd salts up to 40%, 12% and 5%, respectively. In a ternary system, the mesophase range of ~20°C, starting below 80°C, could be obtained at ~25% gadolinium salt concentration.